Exploring the torque- velocity relationship in postmenopausal women: Analyzing the influence of data processing - Jessica Rial-Vázquez; Alejandra Camacho-Villa; Sonia Liliana Rivera-Mejía; Iván Nine; María Rúa-Alonso; Juan Fariñas; Borja Revuelta-Lera; Eliseo Iglesias-Soler (PLoS ONE, 2025)
Objective The main aims of this study were to compare the goodness of fit and derived parameters of linear and non-linear models for fitting the torque-velocity (TV) relationship in postmenopausal women, and to examine the influence of data processing on the results obtained. Methods Sixteen physically active postmenopausal women completed the experiment. Knee extensor (KE) and elbow flexor (EF) muscle strength was evaluated in the dominant limb using an isokinetic dynamometer. Isometric and isokinetic tests were conducted at 30, 60, 120, 180, 240, and 300°/s. Peak torque and the corresponding joint angles were recorded for each test. TV data were fitted using linear, quadratic polynomial (PM), and Hill’s (HM) regression models. TV relationships were analyzed using both actual data (i.e., the velocity achieved and its associated torque; TVA) and target data (i.e., the velocity preset on the dynamometer and the torque reported; TVT). TV parameters derived from each model and their goodness of fit were calculated for both TVA and TVT relationships. Results The goodness of fit and the estimated TV parameters derived from the regression models differed significantly between TVA and TVT for both KE and EF (P < 0.05). For TVA, the models with the best fit were HM for KE and PM for EF. However, HM yielded unrealistically high theoretical maximum velocity values (6764.69 ± 11619.09°/s) for KE. Parameter estimates for TVA differed significantly between models (P < 0.001). Conclusion Caution is advised when performing isokinetic assessments at high velocities in middle-aged women. The obtained data should be carefully examined, as TVA and TVT should not be used interchangeably. The choice of model can influence the estimated parameters. We recommend using quadratic polynomial models to fit TV data for both KE and EF in postmenopausal women.